Pilipinas A to Z a barangay activity book : all you need to know and do to begin understanding Pilipinas - Solis, Melchizedek Maraon (Giraffe Books, 1997)
An introduction to Philippine culture and history, it is arranged alphabetically. Each topic has basic information as well as a short discussion of relevant issues in boxed texts. Maps and black and white illustrations are in almost every page. At the beginning of each topic is a Filipino saying or salawikain. At the end of each topic is a suggested activity for the barangay and a list of sources. Topics range from the Philippine archipelago, Filipino epics, festivals, heroes, to Philippine-American relations. Time period is from pre-Spanish to mid-1980s, with the bulk of the data focusing on the Spanish and early American period.